2002
DOI: 10.1038/sj.ijo.0801943
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mild cold exposure on UCP3 mRNA expression and UCP3 protein content in humans

Abstract: OBJECTIVE:In rodents, adaptive thermogenesis in response to cold exposure and high-fat feeding is accomplished by the activation of the brown adipose tissue specific mitochondrial uncoupling protein, UCP1. The recently discovered human uncoupling protein 3 is a possible candidate for adaptive thermogenesis in humans. In the present study we examined the effect of mild cold exposure on the mRNA and protein expression of UCP3. SUBJECTS: Ten healthy male volunteers (age 24.4 AE 1.6 y; height 1.83 AE 0.02 m; weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Another potential mechanism in humans is uncoupling by UCP-3, a UCP-1 homolog that is present in skeletal muscle tissue. However, it has been shown that the UCP-3 protein content and mRNA expression have not been increased after mild cold exposure (41). On the other hand, FFA are known to stimulate UCP-3 activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism in humans is uncoupling by UCP-3, a UCP-1 homolog that is present in skeletal muscle tissue. However, it has been shown that the UCP-3 protein content and mRNA expression have not been increased after mild cold exposure (41). On the other hand, FFA are known to stimulate UCP-3 activity (42).…”
Section: Discussionmentioning
confidence: 99%
“…While no changes were observed in the BAT-specific transcripts in the subcutaneous adipose tissue, it is possible that longer duration of exposure to 19 °C could stimulate transcription of BAT-specific genes (35, 36). However, the actual contribution of BAT to the maintenance of energy balance in humans has not been empirically demonstrated, and it is possible that other tissues such as skeletal muscle may play a major role in adaptive thermogenesis in adult humans (37). …”
Section: Discussionmentioning
confidence: 99%
“…However, UCP3 mRNA expression is down regulated, suggesting that prolonged cold exposure also decreases UCP3 protein content. Thus, this result indicates that, although basal UCP3 protein content is related to energy metabolism, the function of UCP3 is not in the adaptation to cold (Schrauwen et al 2002c). Recently, de Lange et al (2001) reported evidence of a role for UCP3 in thyroid hormone-induced thermogenesis.…”
Section: Uncoupling Protein 3 Is Related To Energy Expenditure In Hummentioning
confidence: 91%